Visual Deficiency in Wallenberg"s Syndrome : Wallenbergov sindrom i poremećaj vida - Bjeloš, Mirjana (Array, 2021)
The aim of this case report of a 47-year-old woman who suffered from acute right-sided medullar ischemic stroke was to define the range of visual impairment in Wallenberg"s syndrome (WS). The patient complained of unbearable environmental tilt and rotating visual perception. On examination, 11 months following the stroke, the patient manifested rightsided postural inclination and gaze ipsipulsion. The fixation in primary position was unstable, after a conjugate ipsipulsion ensued, spontaneous corrective saccades and a horizontal-rotational jerking nystagmus beating away from the side of the lesion were generated. Monocular visual acuity (right eye: 0.4 logMAR distance and 0.2 logMAR near; left eye: 0.1 logMAR distance and 0.0 logMAR near) was significantly better than binocular (0.63 logMAR distance and near). Fluent reading was impossible. Contralateral smooth pursuits were more impaired. Saccades were defective manifesting right hypermetria and left hypometria. Visual field was constricted to central 10 – 20°. A diagnosis of Wallenberg"s syndrome was made. Occlusion was prescribed. Review of literature demonstrated lack of evidence-based guidelines for ophthalmic assessment and treatment of visual impairment in WS. Oculomotor abnormalities, oscillopsia and tilt illusion cause significant impact to daily life. Early post-stroke ophthalmological evaluation is thus mandatory in order to offer timing treatment.